2009
DOI: 10.15835/nsb113489
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Humic Acid on Nutrient Composition in Broad Bean (Vicia faba L.) Roots

Abstract: Humic acids promote the conversion of mineral nutrients into forms available to plants. It also stimulates seed germination and viability, and its main effect usually being more prominent in the roots. The objective of this study was to determine of the influence of humic acid on broad bean (Vicia faba L.) cultivar ‘Eresen 87’ on root growth and development as well as nutrient uptake, during investigation in a pot experiment. Treatment with leonardite, as humic acid source positively affected both germination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 30 publications
5
30
1
6
Order By: Relevance
“…The increase was ~1.36 (100 ppm), ~1.88 (200 ppm), ~2.30 (300 ppm) and ~2.77 (400 ppm) fold, respectively. Our results are in agreement with that of Akinci et al (2009), they also reported that the humic acid applications increased calcium concentration in broad been roots, and same was reported in tomato by David et al (1994).…”
Section: Calcium (Ca)supporting
confidence: 93%
See 3 more Smart Citations
“…The increase was ~1.36 (100 ppm), ~1.88 (200 ppm), ~2.30 (300 ppm) and ~2.77 (400 ppm) fold, respectively. Our results are in agreement with that of Akinci et al (2009), they also reported that the humic acid applications increased calcium concentration in broad been roots, and same was reported in tomato by David et al (1994).…”
Section: Calcium (Ca)supporting
confidence: 93%
“…Our results support that of Akinci et al (2009), who found that the Fe 3+ increased in humic acid treated broad bean roots as compared to the control. In tomato plants grown in green house conditions, applying humic acid increased the Fe 3+ content in its roots (David et al, 1994).…”
Section: Iron (Fe)supporting
confidence: 92%
See 2 more Smart Citations
“…Humic acid is a product contains many elements which improve the soil fertility and increase the availability of nutrient elements by holding them on mineral surfaces and, consequently, affect plant growth and yield (Hartwigson and Evans, 2000, Hafez, 2004and Akinci et al, 2009. Nowadays, it is mostly used to eradicate or decrease the negative effects of chemical fertilizers and some other chemicals from the soil (Salman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%